Monochromatic sums and products - Green, B; Sanders, T (Alliance of Diamond Open Access Journals, 2016)
Suppose that Fp is coloured with r colours. Then there is some colour class containing at least cr p 2 quadruples of the form (x, y, x+y, xy).